Biologics in Rheumatoid Arthritis: When & Why? - Islam, Md Nazrul (Bangladesh Journal of Medicine, 2023)
Among the autoimmune rheumatic diseases RA is common. Not only articular extra-articular manifestations are common including involvement of skin, ocular, haematological, pulmonary and renal systems. A heightened cardiovascular risk also exists which closely follows disease activity stresses to obtain remission or low disease activity. Therapeutic landscape of RA treatment most significantly shiftedwith the introduction of biological disease modifying anti-rheumatic drugs (bDMARDs). There are five classes of bDMARDs currently available, each with a different molecular target and subtle differences in their efficacy and safety profile. Patient with poor prognostic factors and failed to csDMARDs are the candidate of anti-TNF agents and or other biologics. Clinicians should screen for latent infections with hepatitis B and C serology, chest radiograph plus interferon gamma release assay or tuberculin skin test. In the indicated cases, HIV serology should be requested as well. To reduce infection risk, guidelines specify that patients on bDMARDs should continue with national vaccination schedules including influenza and pneumococcal immunisations as well as the HPV vaccine for cervical cancer. Live attenuated vaccines (like, live herpes zoster vaccine, yellow fever, measles, mumps, rubella), are contraindicated in patients taking a bDMARD. The contraindications of anti-TNF agent’s initiations are serious or untreated infections including TB, current malignancy, multiple sclerosis, severe heart failure and hypersensitivity. In case of tocilizumab contraindications are serious or untreated infections, hypersensitivity and diverticulitisand for rituximab reactivation of hepatitis B.Coadministration of one class of bDMARD with another from a different class is not recommended due to an increased risk of infection. A DAS28 reduction of <1.2 should be considered as improvement at 3 and 6 monthvisits. A close monitoring is advocated for the adverse effects of biologic agents. TNF inhibitors may be continued during pregnancy. Rituximab, abatacept and IL-6 inhibitors are not safe in first trimester. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 193-194